TRADISI PERKAWINAN DI KENEGERIAN KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Fauzia Rahmadani; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted in Kenergian Kari, Central Kuantan District. The purpose of this research is (1)to find out how the of implementing the marriage tradition in Kenegerian Kari and (2)how is the change tradition of marriage in Kenegerian Kari. The method used in this research is a qualitative method by presenting the descriptive analysis with points on observation and natural conditions. The subjects of this study were determined by purposive sampling technique and data collection techniques using observation, interviews and documentation of the results of the study showed that the shift in the traditional system in Kenegerian Kari lies in the change tradition of marriage. In ancient times, starting from the introductory stage, Batando, Potang Balongkok (cooking), Delivering Goats, marriage contracts, marriage parties, and post-marriage are still carried out normatively, but nowadays it leads to a more practical implementation, as for a shift in the traditional system. which is located at the stage of implementing the introduction, Batando, delivering the Goat, night bainai, wedding party which is carried out in a modern and practical manner. As well as the factors that cause the change in tradition, namely the development of science, economic factors, and developmental factors.Keywords: Change, Tradition, Marriage